Recess at 20 below - Aillaud, Cindy Lou, 1955- (Alaska Northwest Books, 2005)
How cold does it have to be before Alaskan kids stay inside for recess? This is a photo book with text written from a child's perspective on what kids do during recess at 20 below. We see kids getting ready for recess, putting on layers of outdoor clothing, and then somebody has to go to the bathroom! Going sledding, swinging, running around outside with frosted-up eyelashes and face masks.